Menu Patterns, Food Acceptability, and Lunch Preferences among Female Students - Putri, Dhifa Cahyani Dwi; Hapsari, Indri (Journal of Local Therapy, 2025)
This study aims to examine the menu patterns, food acceptability, and lunch preferences among female students of ICBS Wustha Al Muflihun, Malang. A descriptive qualitative research design with a cross-sectional approach was employed. Data collection used modified observation and interview methods. A total of 34 students were selected from 52 using purposive sampling. The study found that the lunch menu patterns were generally unbalanced, consisting only of staple food, plant-based side dishes, and vegetables. Food acceptability was categorized as good, with an average leftover percentage of 6.53%. Regarding preference, 67% of students liked the taste, 56% liked the color and aroma, and 64% liked the texture. It is suggested that school lunch providers consider a more balanced menu and improve variation to increase acceptance and nutritional adequacy.